Acupuncture as adjunctive therapy for patients with AECOPD: study protocol for a multicenter, randomized controlled trial - Yang, Chunyan; Sun, Mingsheng; Xu, Guixing; Luo, Qin; Huang, Liuyang; Tian, Hao; Gong, Siyao; Li, Qian; Yu, Xin; Chen, Ming; Huang, Dan; Liu, Yilin; et al. (Frontiers in Public Health, 2023)
Background The acute exacerbation of chronic obstructive pulmonary disease (AECOPD) is a common respiratory disease among older adults, which imposes a significant burden on individuals and society and poses a major challenge to the global public health system due to its high morbidity and mortality. Acupuncture is effective for AECOPD, but its efficacy has been questioned due to the limited methodological quality. Thus, we aim to investigate the efficacy of acupuncture as adjunctive therapy for AECOPD and determine whether the efficacy of acupuncture differs with the type of acupoint combinations. Methods and analysis This study proposes a prospective, multicenter randomized controlled trial that will comprise four groups, including two acupuncture treatment groups, one sham acupuncture group, and one basic treatment group. The acupuncture treatment groups will be distinguished by their focus on different patterns of acupoint combination, namely the Xi-cleft and He-sea acupoint combination and the Eight Confluence points acupoint combination, which may vary in clinical efficacy based on traditional acupuncture theories. The study aims to randomize 556 patients in a 1:1:1:1 ratio across the four groups. Each patient in acupuncture group or sham acupuncture group will receive routine drug therapy and 7 sessions of acupuncture treatment over 1 week. Participants in the basic treatment group will only receive routine drug therapy. The trial will be conducted in seven hospitals located in China. The primary outcomes in this trial will include differences in the Breathlessness, Cough, and Sputum Scale (BCSS) before randomization, 7 days after randomization, 5 and 9 weeks after randomization. Ethics and dissemination Ethical approval was obtained from the Sichuan Regional Ethics Review of Committee on Traditional Chinese Medicine (Approval ID: 2022KL-068). The results of this study will be distributed through peer-reviewed journals. Clinical Trial Registration: ClinicalTrials.gov, identifier ChiCTR2200064484.